Pengaruh Kompensasi Dan Kompetensi Terhadap Kinerja Karyawan Pada PT. Oasis Water Internasional Banyuansin Sumatera Selatan - Junianto, Rizal; Afriyani, Fauziah; Lazuarni, Shafiera (Politeknik Negeri Ambon, 2024)
The aim of this research is to identify the relationship between the performance of PT Oasis Water International workers and factors such as compensation and competition. All employees of PT. Oasis Water International was the focus of this quantitative research, with a total of 160 people and 115 of them filled out the survey using a simple random sampling method based on the Slovin formula. PT employees. Oasis Water International was given a questionnaire to fill out to collect data. Multiple linear regression was used to analyze the data, using SPSS 24 to manage research data. Based on the research results, employee performance is influenced positively and significantly by the compensation variable. This is supported by a Tcount value of 4.361 and a TTable value of 1.981, which shows that Tcount > TTable (4.361 > 1.981), with a significance level of 0.000 < 0.05. Compensation has a significant influence on productivity in the workplace. Tcount > TTable (13.101 > 1.981), sig. 0.000 < 0.05 indicates that the competency variable has a significant positive effect on employee performance. These findings indicate that competency and compensation partially have a significant effect on the performance of PT employees. Oasis Water International. Based on the results of the F test, the significance level was obtained at 0.000 < 0.005 and Fcount > fTable (85.242 > 3.08). Compensation and competency both have a positive effect on the performance of PT Oasis Water International workers so they have a simultaneous effect